Genocide and political destruction in Tigray: The imperative for systemic transformation - Alemu, Muauz Gidey (Journal of Governance and Accountability Studies, 2024)
Purpose: This study examines the severe governance and public service challenges in the Tigray region of Ethiopia following genocide and political destruction, aiming to analyze the impact of the conflict on governance structures and advocate for transformative frameworks. Methods: A qualitative survey involving 2,280 respondents was conducted using systematic random sampling and snowballing, with data collected through semi-structured interviews, focus group discussions, and field observations, analyzed using ATLAS.ti version 9. Results: The findings revealed significant gaps between public expectations and government performance, highlighting political destruction, governance collapse, and deteriorating public services. Importantly, the research underscores the often-overlooked invisible damage to political systems that perpetuate ongoing violence and societal decay. Limitations: This study emphasizes the need for governance and political transformation that enhances accountability, transparency, and citizen engagement to prevent further political decay, calling for coordinated governance strategies aligned with democratic principles to empower citizens and contribute to Tigray's recovery, sustainable development, and social cohesion. Contributions: This study contributes to the theoretical and empirical body of knowledge on the impact of genocide on politics and governance and the strategies for the post-genocide transformation of governance and society.